Menuju Rekam Medis Elektronik: Seberapa Jauh Kesiapan Klinik? - Aryanti Desty Ramadhani; Anton Kristijono; Niko Tesni Saputra (Journal of Health Information Management and Medical Record, 2025)
Medical records have been urged by requiring health care facilities, including clinics, to organize electronic medical records. The implementation of Electronic Medical Records needs to be done by analyzing readiness first. The analysis can be done using the DOQ-IT method. Readiness analysis is needed before implementing RME to determine the level of RME readiness at the Primary Clinic of the Poltekkes Kemenkes Yogyakarta based on the Docto's office quality-information technology (DOQ-IT) method. This type of research is descriptive with a quantitative approach accompanied by qualitative. Research data were collected through questionnaires using googleform and in-depth interview guidelines. The sample used was total sampling of 15 respondents and 1 informant. Primary Clinic of Poltekkes Kemenkes Yogyakarta is very ready (119.71) in implementing RME. Judging from human resources, the clinic is quite ready, with an average score of 3.78. Judging from the organizational work culture, the clinic is very ready, with an average score of 4.31. In terms of leadership, the clinic is very well prepared with an average score of 4.03. In addition, seen from the infrastructure, with an average score of 4.23. Of the four components, the HR component has a fairly low value so that in-depth exploration is needed. The Primary Clinic of the Poltekkes Kemenkes Yogyakarta obtained a score of 119.71, which is said to be very ready. The strategy in dealing with Electronic Medical Records in the conditions of the Primary Clinic of the Poltekkes Kemenkes Yogyakarta is to take advantage of the internship program with third parties and form a special team responsible for supporting the implementation of electronic medical records.